The Effect of STEM (Science, Technology, Engineering, and Mathematics) based Textbooks in Biotechnology Learning Material on The Critical Thinking Skills and Learning Results of Senior High School Students in The Industrial Agriculture Area - Khoiroh, Kamilatul; Siswati, Bea Hana; Fikri, Kamalia (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The study entitled the effect of STEM (Science, Technology, Engineering, and Mathematics) based textbooks in biotechnology learning material on the critical thinking skills and learning results of senior high school students in the industrial agriculture area. The purpose of this study was to determine the effect of STEM-based textbooks on the subject of biotechnology on critical thinking skills and student learning outcomes in industrial agriculture areas. This type of research is quasi-experimental research (quasi experiment). The sampling technique was carried out through the normality test and ANOVA homogeneity test using the end of semester exam scores for biology subject then the determination of the sample was carried out randomly (random sampling). The research samples were class XII MIPA 2 as the experimental class and XII MIPA 4 as the control class. The place of this research is at SMAN 3 Jember. Data analysis used the covariance analysis test (Anacova) and Independent Sample T-Test for data that met the parametric test requirements, namely normal and homogeneous. The significance value obtained was <0.05 so it can be concluded that there is an influence of STEM (Science, Technology, Engineering, and Mathematics) based textbooks on the subject of biotechnology on critical thinking skills and learning outcomes.